Simon Peter in the Gospel according to John: His Historical Significance according to the Johannine Community's Narrative - Christos Karakolis (Analogia: The Pemptousia Journal for Theological Studies, 2020)
In the interconfessional theological dialogue between the Orthodox and the Roman-Catholic Church, there has been much discussion about the famous passage 16:16–19 of Matthew’s Gospel. However, not much attention has been paid to the testimonies of other New Testament books about the Apostle Peter’s person, work, and historical impact. This paper examines the narrative character of Simon Peter in John’s Gospel to contribute to a more comprehensive understanding of the great apostle’s historical significance in early Christianity. In our analysis, we make use of the narrative-critical method focusing on the comparison between Simon Peter and the Beloved Disciple. This approach opens a window to how the Johannine community evaluated Peter’s person and significance at the time of the composition of the Fourth Gospel, and, thus, helps us better understand the biblical foundations of the theological debate on the papal office.